Collembola diversity in Portuguese forest stands : deriving surrogates for species richness and evaluating the effects of forest type and grazing - Reis, Filipa Alexandra da Ferreira (2014)
Dissertação de mestrado em Ecologia, apresentada ao Departamento de Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.